2
$\begingroup$

Find $$\min\{a_1x_1^2 + a_2x_2^2\}$$ Where $ a_1x_1 + a_2x_2 = B$, and $a_1>0$ and $a_2>0 $. Find $x_1$ and $x_2$.

Can we do it usig AG mean inequality?

Let's say we have the problem to find the minimum value of $ x_1^2 + x_2^2 $.

From: $ (x_1 - x_2)^2 ≥0 $, $ x_1^2 + x_2^2 ≥ 2x_1x_2 $

So the minimum value is: $2x_1x_2 $ for $x_1=x_2$.

Can be this done in a simillar manner for the starting problem.

why cannot we put $ x^2 =a_1 x_1^2, y^2 =a_2 x_2^2$ and solve it like root mean square inequality (without generalization?) We get: $x^2 = y^2 $
. $ a_1 x_1^2 = a_2 x_2^2 $

but not $x_1 = x_2$?

$\endgroup$
9
  • 2
    $\begingroup$ I don't see what this has to do with AG. Seems like a Lagrange multiplier problem... $\endgroup$ May 5 at 18:00
  • 1
    $\begingroup$ I mean: $ \sqrt((x_1^2 + x_2^2)/2) >= (x_1+x_2) /2 $ $\endgroup$ May 5 at 18:13
  • $\begingroup$ Would you like to add your any attempts to the question? $\endgroup$ May 5 at 18:49
  • 1
    $\begingroup$ @BlueSkiesHighFlyer Lookup the weighted power mean inequality, which generalizes the root mean square inequality. You would get $\sqrt{(a_1x_1^2+a_2x_2^2)/(a_1+a_2)} \ge (a_1x_1+a_2x_2)/(a_1+a_2)$. $\endgroup$
    – dxiv
    May 5 at 19:56
  • 1
    $\begingroup$ @BlueSkiesHighFlyer Write down the RMS inequality with your substitution and you'll realize that the right hand side is not what you need i.e. not a constant. $\endgroup$
    – dxiv
    May 5 at 20:56
3
$\begingroup$

Use standard algebra:

We have,

$$\begin{align}a_1x_1^2+a_2x_2^2&=a_1\left(\frac{B-a_2x_2}{a_1}\right)^2+a_2x_2^2\\ &=\frac{B^2-2Ba_2x_2+a_2^2x_2^2}{a_1}+a_2x_2^2\\ &=\left(a_2+\frac{a_2^2}{a_1}\right)x_2^2-\left(\frac{2Ba_2}{a_1}\right)x_2+\frac{B^2}{a_1}\end{align}$$

This is the quadratic polynomial. You can minimize the quadratic polynomial with the following method:

$$ax^2+bx+c=a(x-m)^2+n$$

where, $$m=-\frac{b}{2a}, ~ n=-\frac{b^2-4ac}{4a}$$


In this case, we have

$$\begin{align}a:=a_2+\frac{a_2^2}{a_1}, ~b:=-\frac{2Ba_2}{a_1} , ~c:=\frac{B^2}{a_1}\end{align}$$

Hence we get,

$$m:=\frac{B}{a_1+a_2},~ n:=\frac{B^2}{a_1+a_2}$$

Thus,

$$\begin{align}a_1x_1^2+a_2x_2^2=\left(a_2+\frac{a_2^2}{a_1}\right)\left(x_2-\frac{B}{a_1+a_2}\right)^2+\frac{B^2}{a_1+a_2}\end{align}$$

Finally, we conclude that $$\min\left\{a_1x_1^2+a_2x_2^2 \mid a_1x_1+a_2x_2=B\right\}=\frac{B^2}{a_1+a_2}$$ which is attained at the point $x_1=x_2=B/(a_1+a_2)$.

$\endgroup$
13
  • $\begingroup$ Thanks, but can we do it without using quadraric equation, just the inequality? $\endgroup$ May 5 at 18:21
  • $\begingroup$ @BlueSkiesHighFlyer This is the algebraic method I know. I don't know any other, unfortunately. $\endgroup$ May 5 at 18:47
  • 1
    $\begingroup$ I would consider using features of Markdown to emphasize that sentence, like the alternative I edited in. Not sure, which is best. Also a matter of taste, so I quite understand, if you don't like my suggestion. Furthermore, I cannot test this with the mobile view, for I am too old to understand why anybody would use this site with a screen smaller than 15 inches :-) $\endgroup$ May 6 at 6:32
  • 1
    $\begingroup$ (perhaps "which is attained" is better) $\endgroup$ May 6 at 7:50
  • 1
    $\begingroup$ It's fine as it is, I think. $\endgroup$ May 6 at 18:16
2
$\begingroup$

I see there's nothing calculus-ish in the tags, so maybe a proof using calculus isn't allowed. If so then it's allowed here:

Lagrange multipliers. $f=a_1x_1^2+a_2x_2^2$, $g=a_1x_1+a_2x_2$, and we want $\nabla f=\lambda\nabla g$: $$\begin{align}2a_1x_1=\lambda a_1, \\2a_2x_2=\lambda a_2,\end{align}$$hence $x_1=x_2$, so $x_1=\dots$ and $x_2=\dots$.

$\endgroup$
4
  • $\begingroup$ why cannot we put $ x^2 =a_1 x_1^2, y^2 =a_2 x_2^2$ and solve it like root mean square inequality (without generalization?) We get: $x^2 = y^2 $ . $ a_1 x_1^2 = a_2 x_2^2 $ but not $x_1 = x_2$? $\endgroup$ May 5 at 20:52
  • $\begingroup$ @BlueSkiesHighFlyer I didn't say you couldn't solve it that way. If you don't get this then I'm pretty sure your answer's wrong, because this is so simple... Oh: also this is the same as the other answer above. $\endgroup$ May 5 at 20:54
  • $\begingroup$ So what is the mistake in these two lines? $ a_1 x_1^2 = a_2 x_2^2 $ but not $x_1 = x_2$? $\endgroup$ May 5 at 20:57
  • $\begingroup$ @BlueSkiesHighFlyer I'm not going to worry about trying to find the error, sorry. $\endgroup$ May 5 at 21:02
1
$\begingroup$

Going along your lines, we can write \begin{align} &a_1a_2(x_1-x_2)^2\ge0\\ \iff&a_1a_2(x_1^2+x_2^2)\ge 2a_1a_2x_1x_2\\ \iff&a_1^2x_1^2+a_2^2x_2^2+a_1a_2(x_1^2+x_2^2)\ge a_1^2x_1^2+a_2^2x_2^2+2a_1x_1a_2x_2\\ \iff&(a_1x_1^2+a_2x_2^2)(a_1+a_2)\ge(a_1x_1+a_2x_2)^2\\ \iff&a_1x_1^2+a_2x_2^2\ge\frac{B^2}{a_1+a_2} \end{align} This is the required lower bound.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.